Open Reduction With Speed's Triceps V-y Plasty Technique in Old-unreduced Posterior Fracture-dislocation of Elbow - Karakurt, Lokman; Ekinci, Ahmet; Köse, Rüştü (Fırat University, 2003)
In an old-unreduced fracture-dislocation, reduction is difficult mostly because of soft tissue contracture, scar tissue and new bone formation. None of these treatment options are entirely satisfactory. These options include closed reduction, open reduction, excision arthroplasty, interposition arthroplasty and arthrodesis. 11 years old boy was diagnosed 40 days old unreduced posterior fracture -dislocation of his right elbow. The boy was treated with open reduction with Speed's triceps V-Y plasty technique. The cast and kirschner wires were removed three to six weeks after the operation. After the rehabilitation period the elbow had a 105º of flexion range. As a result, Speed's triceps V-Y plasty technique is a successful method in old unreduced fracture-dislocation of elbow in children.

Eski dirsek kırıklı-çıkıklarında redüksiyon yumuşak doku kontraktürü, skar dokusu ve yeni kemik formasyonundan dolayı zordur. Tedavi seçeneklerinden hiçbiri tamamıyla yüz güldürücü değildir. Bu tedavi seçenekleri; kapalı redüksiyon, açık redüksiyon, eksizyon/interpozisyon artroplastileri ve artrodezdir. 11 yaşındaki erkek çocuğuna, 40 günlük sağ dirsek lateral epikondil kırığı ve posterolateral dirsek çıkığı tanısı kondu. Hastaya Speed'in V-Y uzatma tekniği ile açık redüksiyon yapıldı. Ameliyat sonrası 3. haftada alçısı ve 6. haftada K-telleri çıkarılan hastada, rehabilitasyon sonunda 105° dirsek hareket genişliği sağlandı. Sonuç olarak; Speed'in triseps V-Y uzatma tekniği çocuk eski dirsek çıkıklarında başarıyla uygulanabilecek bir yöntemdir.
Dirsek Gecikmiş Posterior Kırıklı-çıkığında Speed'in Triseps V-y Uzatma Tekniği ile Açık Redüksiyon: Olgu Sunumu